Park cool island modifications to assess radiative cooling of a tropical urban park - Graces N.Y. Ching; Sin Kang Yik; Su Li Heng; Beatrice H. Ho; Peter J. Crank; Moshe Mandelmilch; Xiang Tian Ho; Winston T. L. Chow (Scientific Reports)
Abstract Many cities experience urban overheating from climate change and the urban heat island phenomenon. Previous studies demonstrate that parks are a potential nature-based solution to mitigate urban overheating through the ‘Park Cool Island’ (PCI) effect. PCI intensity can be measured through field measurements (FM) or remote sensing. This FM study used a network of meteorological sensors within a park and in its surrounding urban area to ascertain its PCI intensity in Singapore from January to December 2022. Consistently cooler air temperatures were found throughout a 24-h period in the park area, with mean daytime (nighttime) PCI intensity measured ~ 2.21 °C (~ 1.69 °C). A modified version of PCI (PCImodified) was developed to highlight the radiative cooling differences between the urban and park areas. PCImodified leverages on the network of sensors to preserve the spatial granularity of data, allowing for the interpolation of point data across the study area. By employing Geographical Information Science concepts, the model visualises the diurnal changes in PCImodified intensities with respect to tree height, tree density, and building height; significant cooling is positively (negatively) correlated with tree height and density (building height). This study demonstrates a comprehensive analysis of PCI and cooling intensities of parks using FM in understudied tropical urban environments.